Association Between Serum Follicle-Stimulating Hormone and Sarcopenia and Physical Disability Among Older Chinese Men: Evidence From a Cross-Sectional Study - Ke, Yingying; Xu, Jun; Zhang, Xiaoyan; Guo, Qihao; Zhu, Yunxia (Frontiers in Medicine, 2022)
Background: Sarcopenia is a geriatric syndrome characterized by progressive loss of muscle mass, function and quality and associated with a range of adverse health outcomes including disability. Despite a negative correlation between muscle mass and follicle-stimulating hormone (FSH) levels in postmenopausal women, it is unclear if FSH is associated with sarcopenia and its poor outcomes, especially in older men. Methods: We used cross-sectional data from 360 men aged over 80 who participated in health check-ups to investigate correlations between serum FSH and sarcopenia, individual sarcopenia components, low physical performance (gait speed ≤ 0.8 m/s) and instrumental activities of daily living (IADL) disability. Sarcopenia was diagnosed according to the revised definition of the European Working Group on Sarcopenia in Old People (EWGSOP2). Results: The prevalence of sarcopenia was 17.8% in this population. Compared with high FSH group, low FSH group showed a significant reduction in the risk of having sarcopenia (OR 0.346, 95% CI 0.131-0.912, P = 0.032) and low calf circumference (a surrogate for muscle mass, OR 0.216, 95% CI 0.083-0.559, P = 0.002) after adjusting for age, waist circumference, education, exercise, and associated biochemical parameters including other sex hormones in binary logistic regression analysis. Further adjusting for C-reactive protein led to loss of the association between FSH and sarcopenia (OR 0.507, 95% CI 0.174-1.477, P = 0.213), but not between FSH and low calf circumference (OR 0.312, 95% CI 0.111-0.877, P = 0.027). No associations were observed between FSH and sarcopenia severity, low handgrip strength, low physical performance, and disability in fully adjusted models. Conclusion: In older men, circulating FSH was positively associated with sarcopenia, although this association was partially dependent on chronic low-grade inflammation. Moreover, FSH was an independent risk factor for low muscle mass. Therefore, FSH blocking may be a feasible therapeutic target toward maintenance of skeletal muscle quantity and prevention of sarcopenia in aging men.